2021
DOI: 10.3390/cancers14010202
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of PIWI-Interacting RNAs (piRNAs) in Gastrointestinal Cancers: An Updated Perspective

Abstract: Gastrointestinal (GI) cancers produce ~3.4 million related deaths worldwide, comprising 35% of all cancer-related deaths. The high mortality among GI cancers is due to late diagnosis, the presence of metastasis and drug resistance development. Additionally, current clinical markers do not adequately guide patient management, thereby new and more reliable biomarkers and therapeutic targets are still needed for these diseases. RNA-seq technology has allowed the discovery of new types of RNA transcripts including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…PiRNAs are a novel class of short chain ncRNAs (26-30 nucleotides) involved in a wide variety of physiological and pathological processes. They can regulate the expression of somatic genes through various mechanisms, including DNA methylation, chromatin modification and transposon silencing ( 229 , 230 ). An increasing amount of evidence suggests that piRNAs are key regulators in the development of cancer drug resistance ( 231 233 ).…”
Section: Mechanisms Of Ncrnas In Mediating Cancer Drug Resistancementioning
confidence: 99%
“…PiRNAs are a novel class of short chain ncRNAs (26-30 nucleotides) involved in a wide variety of physiological and pathological processes. They can regulate the expression of somatic genes through various mechanisms, including DNA methylation, chromatin modification and transposon silencing ( 229 , 230 ). An increasing amount of evidence suggests that piRNAs are key regulators in the development of cancer drug resistance ( 231 233 ).…”
Section: Mechanisms Of Ncrnas In Mediating Cancer Drug Resistancementioning
confidence: 99%
“…RNAs are divided into coding RNAs (mRNAs) and non-coding RNAs based on whether they can encode proteins. Studies have shown that mRNAs account for less than 2% of the total genome, and more than 98% are ncRNAs, such as lncRNAs, miRNAs, circRNAs, small nucleolar RNAs (snoRNAs) [ 35 ], tRNA-derived small RNAs [ 36 ], and piwi-interacting RNAs [ 37 , 38 ]. At a time when ncRNAs were poorly understood, they were considered nonfunctional “junk” [ 39 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Except for the exosomal miRNAs, lncRNAs and circRNAs, some other ncRNAs, including tRNA-derived small RNAs [ 36 ] and piwi-interacting RNAs [ 37 , 38 ], also participate in tumorigenesis. Due to the lack of adequate literature, we do not make too much of an elaboration here.…”
Section: Function Of Exosomal Circrnas In Hccmentioning
confidence: 99%
“…On the other hand, aberrantly expressed ncRNAs are closely related with the pathogenesis of various diseases such as cancers. Under complex cancer conditions, the deregulation or dysfunction of ncRNAs has been reported to affect multiple cellular processes in almost all major cancers [ 4 , 5 , 6 , 7 ]. The roles of cancer-involved ncRNAs such as miRNA, lncRNA and circRNA have been extensively studied, and their potential mechanisms in cancer development are progressively being established [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%